Legal and jurisdictional guidebook for coastal resource management in the Philippines. (Manila, Philippines CRMP, 1997)
CRMP Document No. 8-CRM/1997
Keywords: Coastal resource management--Handbooks, manuals, etc.--Philippines.; Coastal resource management--Legal status, laws, etc.--Philippines.; Coastal resource management--Legislation--Philippines.